Diet-Driven Microbial Dynamics, Pathogen Profiles, and Transcriptomics in Bats: Bioinformatics Insights Into Gut Microbiomes and Gene Expression - Muhd Amsyari, Morni (UNIMAS, 2025)
This thesis reports a comprehensive study of Bornean bats, focusing on their gut microbiome dynamics, pathogenic bacteria, antimicrobial resistance bacteria, and gene expressions from bats of different dietary preferences. Despite the increasing interest in bats as ecological keystone species and potential zoonotic reservoirs, significant gaps remain in understanding their gut microbiomes and functional gene expression, particularly in Southeast Asia. Current studies often overlook the influence of dietary guilds, such as insectivorous and phytophagous diets, on microbial diversity and functional adaptations. Moreover, the role of bat gut microbiota in antimicrobial resistance and zoonotic pathogen transmission remains largely unexplored. Addressing these gaps is crucial for understanding bat health, their ecological roles, and potential public health implications. Firmicutes, Proteobacteria, and Campylobacterota were detected in both insectivorous (insect-based) and phytophagous (plant-based) bats. Both insectivorous and phytophagous groups exhibited no dominant taxon (D = 0.076; = 0.085). The correlation network analysis revealed a negative relationship between Lactobacillus, a type of "good bacteria," and pathogenic bacteria like Salmonella (-0.4124) and Yersinia (-0.4654). Some of the medically important pathogenic bacteria detected were Citrobacter koseri (e.g., infant meningitis), Enterococcus faecalis (e.g., endocarditis), Escherichia coli (e.g., bloody diarrhoea), and Shigella sonnei (e.g., bloody diarrhoea). These bats were detected to be resistant to many antibiotics, such as spectinomycin, tetracycline, kasugamicin, gentamicin, streptomycin, edeine, neomycin, tobramycin, paromomycin, kanamycin, viomycin, and hygromycin B. Through transcriptomic study, it has been identified that bats that prefer a plant-based diet exhibit a highly prevalent genetic expression associated with carbohydrate digestion and vitamin absorption metabolic pathways. In contrast, insectivorous bats emphasised the metabolic pathway for xenobiotics and the immune defence mechanism against pathogenic substances transported by their prey. This study has successfully report and discussed three chapters related to their gut microbiome dynamics, the presence of pathogenic and antimicrobialresistant bacteria, and the genetic expressions linked to various dietary preferences.